Synthesis, structure and properties of N-R-2-(5-(5-methyl-1H-pyrazole-3-yl)-4-phenyl-4H-1,2,4-triazole-3-ylthio)acetamides - A. S. Hotsulia; S. O. Fedotov (Zaporozhye State Medical University, 2019)
Heterocyclic compounds remain the most promising group of compounds, through which the new drugs with characteristic list of properties are successfully created. Examples of this systems are 1,2,4-triazole and pyrazole. The presence in one molecule structure of fragments of two different azaheterocycles is synthetically interesting and allows increasing the probability to obtain biologically active substance with a wide spectrum of action.The aim of the work was to optimize the synthesis conditions and investigate the properties of N-R-2-(5-(5-methyl-1H-pyrazole-3-yl)-4-phenyl-4H-1,2,4-triazole-3-ylthio)acetamides in case of change of chemical process conditions.Methods and results. Ethyl 5-methyl-1H-pyrazole-3-carboxylate, which was obtained by known techniques using acetone, diethyl oxalate, sodium methoxide, followed by hydrazine hydrate in equivalent amount, was used as the key starting reagent. The resulting ethyl 5-methyl-1H-pyrazole-3-carboxylate was used to carry out hydrazinolysis reactions and nucleophilic addition of phenyl isothiocyanate with subsequent alkaline heterocyclicization. The synthesized 5-(5-methyl-1H-pyrazol-3-yl)-4-phenyl-4H-1,2,4-triazole-3-thiole was used in alkylation reactions with promising reagents for the design of pharmacophoric fragments. The products of such reaction are N-R-2-(5-(5-methyl-1H-pyrazole-3-yl)-4-phenyl-4H-1,2,4-triazole-3-ylthio)acetamides. The structure of the resulting compounds was confirmed by elemental analysis, 1H NMR spectroscopy, IR spectrophotometry. The individuality of the substances was determined by thin-layer chromatography and chromatographic mass spectrometry. For synthesized compounds, preliminary screening was performed using the PASS On-line® software and molecular docking.Conclusions. N-R-2-5-(5-methyl-1H-pyrazole-3-yl)-4-phenyl-4H-1,2,4-triazole-3-ylthio)acetamides are obtained with high yields and purity, their properties are investigated.